Model of Educational Leadership Management in Boarding Schools - Dacholfany, Muhammad Ihsan; Ikhwan, Afiful; Budiman, Agus; Hutabarat, Zuhri Saputra (Al-Hayat: Journal of Islamic Education, 2024)
Islamic boarding schools have a wealth of knowledge that can be researched and analyzed from various scientific aspects, so research on Islamic boarding schools will be available. This study will focus on the management pattern of pesantren leadership education by choosing the largest pesantren in the country, namely the Darussalam Gontor Modern Islamic Boarding School. A qualitative method with a case study approach. Data were obtained from key informants, Islamic boarding school documents and books, journals and articles as support related to the management of leadership education in the era of globalization. Data analysis in this study used content analysis techniques. The results of the study found that the management of leadership education in the form of regeneration in the style of the Gontor Islamic Boarding School was classified into six: briefing, training, assignment, habituation, control and role modelling. The revival of leadership values at the Gontor Islamic Boarding School includes education of ibrah, habituation, mauidzah, discipline, independence and exemplary. The pattern of leadership in Darussalam Gontor Islamic Boarding School is collegial (Trimurti). The administration of the Trimurti pesantren Darussalam Gontor became the central figure of the pesantren in the leadership of three kiai. With this collective leadership model, the Gontor Islamic Boarding School will eventually become a modern institution whose survival does not depend on a single kiai as the supreme leader. Thus, Islamic boarding schools are expected to be able to foster and produce Islamic human resources.